Cultivation of character education in the boarding school system: Case study of the tahfiz qur'an islamic islamic boarding school tanjung morawa - Agus Salim; Zailani; Selamat Pohan (At Turots: Jurnal Pendidikan Islam, 2025)
This study aims to analyze the extent to which the concept, as well as inhibiting factors and at the same time analyze efforts to overcome the behavior of students in instilling character education in the boarding school system at the Tahfiz Qur'an Fajar Islam Tanjung Morawa Islamic boarding school. This type of research is descriptive qualitative research, which aims to describe and analyze phenomena related to the instillation of character education in the boarding school system. The main data sources come from teachers, students, and related documents that support the learning process. Data were collected through observation, in-depth interviews, and documentation. The validity of the data was tested through triangulation techniques, by comparing data from interviews, observations, and documentation to ensure the consistency and validity of the findings. Data analysis was carried out through the stages of data condensation, data presentation, and drawing conclusions. The overall results of the study indicate that this Islamic boarding school has succeeded in implementing character education through a systematic and well-organized approach. However, strengthening is needed in the aspects of supervision and evaluation of the implementation of sanctions and rewards, in order to ensure that character values can be applied more consistently and sustainably.